FAUXperience Framework - Designing For Critical Conscious AI Use In Higher Education - DE SOUSA NUNES, JOSÉ BENER (My University, 2024)
requires the development of clear principles for its ethical and responsible use. Despite numerous potential benefits, such as personalized learning and task optimization, this technology poses ethical concerns regarding biases, misinformation, and the difficulty of differentiating human-created texts from AI-generated content. To address these concerns, we created the "FAUXperience Framework" to offer guidelines for the ethical use of AI in education by fostering a critical consciousness about this technology’s potential benefits and risks. The framework results from user research with stakeholders such as teachers, students, and other interested parties. The study focused on collecting qualitative and quantitative data on how stakeholders experience using generative AI tools in their academic activities and how universities handle the issues related to the misuse of AI. The term "FAUXperience" combines "faux," which refers to artificiality, and "experience," to indicate the use of AI to artificially enhance the educational process in addition to traditional teaching methods. By fostering critical consciousness about AI, the framework aims to promote the benefits of learning associated with AI while drawing stakeholders’ attention to its impact on education. In conclusion, the "FAUXperience Framework" encourages teachers and students to be critically conscious actors in AI-powered education.
Keywords: AI; artificial intelligence; FAUXperience Framework; education; critical consciousness; large language models; ChatGPT; critically conscious; ethics